Research of channel quantization and feedback strategies based on multiuser diversity MIMO-OFDM systems - LIANG Xue-jun; ZHU Guang-xi; SU Gang; WANG De-sheng (Tongxin xuebao)
Firstly, a quantization method was proposed by quantized value indicating the modulation level instead of the full values of channel quality information（CQI） and the achievable average spectrum efficiency showed no loss compared with perfect case.Secondly, employment of the integrated design that combined with opportunistic, best, and hybrid feedback scheme was considered and the close-form expression of average spectrum efficiency was deduced in various case.Finally, the calculation of optimal feedback parameters was confirmed from two aspects of feedback channel capacity and capacity relative loss.Extensive simulations were presented to evaluate these proposed strategies.The results match with the numeral analysis very well.The proposed partial feedback schemes can reduce the feedback load greatly with the same system capability, only if the feedback parameters be chosen properly.Wherein, the hybrid feedback combined with quantization performs best and provides the instruction to design the channel feedback of practical systems.